2018
DOI: 10.1186/s41938-018-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification, and molecular diversity of indigenous isolates of Beauveria bassiana from Taif region, Saudi Arabia

Abstract: The entomopathogenic fungus, Beauveria bassiana causes a disease known as the white muscadine disease in insects. Most of the entomopathogenic fungi are soil borne nature an attempt was made to collect the soil samples from various ecosystems. Therefore, the present study aimed to isolate native strains of B. bassiana and study their genetic diversity at Taif region, Saudi Arabia, using ITS of nuclear DNA and COI gene analysis by comparing of different isolates from occasional localities through the world. Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…These 2 sequences were submitted in the NCBI GenBank database with the accession numbers of MN900613 for isolate Bb-Taif1 and MN900614 for isolate Bb-Taif2. In this sense, isolate Bb-Taif1 was identical in the sequence of ITS with previous isolate (accession number: LC338054), which isolated from the soil at the same location (Sayed et al 2018). In our opinion, this finding means that the same isolate in the soil was colonized in the grapevine plants.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…These 2 sequences were submitted in the NCBI GenBank database with the accession numbers of MN900613 for isolate Bb-Taif1 and MN900614 for isolate Bb-Taif2. In this sense, isolate Bb-Taif1 was identical in the sequence of ITS with previous isolate (accession number: LC338054), which isolated from the soil at the same location (Sayed et al 2018). In our opinion, this finding means that the same isolate in the soil was colonized in the grapevine plants.…”
Section: Resultssupporting
confidence: 65%
“…Generally, the virulence of the 2 tested endophytic isolates indicated that the isolate Bb-Taif1 was higher in its virulence than the Bb-Taif2 isolate. Moreover, the findings of molecular characteristic and the virulence in this study and the findings of Sayed et al (2018Sayed et al ( , 2019 showed that the isolate (Bb-Taif1) is endemic in the soil and establishment in the grapevine tissues as an endophytic fungus.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Four genetically different indigenous isolates of B. bassiana (Sayed et al 2018) were used in this study. These isolates were previously isolated from Taif region.…”
Section: Fungus Isolates and Their Mass Productionmentioning
confidence: 99%
“…The isolation of indigenous isolates or strains of EPF from different hosts and locations provides a control program with available specific tools for controlling various indigenous pests (Zayed 2003). Four isolates of B. bassiana were isolated from Taif region (Saudi Arabia) and genetically identified (Sayed et al 2018).…”
mentioning
confidence: 99%